2015
DOI: 10.1111/1440-1681.12398
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peptide YY in blood vessel function and atherosclerosis in a rabbit model

Abstract: Cardiovascular disease remains a burden for Westernized countries. Peptide YY (PYY) raises blood pressure, yet its role has not yet been determined in diseased arteries. This study aimed at identifying PYY and eNOS in diseased blood vessels and to determine which blood vessels respond to PYY. New Zealand White rabbits were fed an atherogenic diet (n = 6, 0.5% cholesterol + 1% methionine + 5% peanut oil) and control animals fed a normal diet (n = 6) for 4 weeks. Immunohistochemistry was used to determine the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(56 reference statements)
2
2
0
Order By: Relevance
“…Consistent with others, we found PYY serum levels to increase with age and to be elevated in patients with diabetes, which has similarly been reported by some [20] although not all investigators [21]. In addition, arterial hypertension was more often present in patients with high PYY levels, which might be attributable to direct vasoconstrictive effects of the peptide resulting in increased blood pressure under experimental conditions [22,23]. Furthermore, more patients with impaired kidney function had elevated PYY levels in our study, which is consistent with earlier findings of elevated PYY levels in patients with terminal renal insufficiency [24].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with others, we found PYY serum levels to increase with age and to be elevated in patients with diabetes, which has similarly been reported by some [20] although not all investigators [21]. In addition, arterial hypertension was more often present in patients with high PYY levels, which might be attributable to direct vasoconstrictive effects of the peptide resulting in increased blood pressure under experimental conditions [22,23]. Furthermore, more patients with impaired kidney function had elevated PYY levels in our study, which is consistent with earlier findings of elevated PYY levels in patients with terminal renal insufficiency [24].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, at P186 when cortical mineralisation was increased in Pyy KO mice, toughness did not differ from WT animals indicating that bone strength and toughness is determined by a complex interplay between cortical diameter, thickness, mineralisation and porosity. Previous studies have shown PYY mediates vasoconstriction via Y1 or Y2 receptor [42] consistent with the increased cortical vessel size in P186 Pyy KO mice . Furthermore, the increase in cortical vessel number in P70 Pyy KO mice suggests PYY may also inhibit angiogenesis during bone growth.…”
Section: Discussionsupporting
confidence: 73%
“…On the other hand, species from Proteobacteria produce serotonin, NE, and DA [170], which are neurotransmitters with pro-hypertensive and pro-atherogenic properties [171][172][173], with the exception of DA [174][175][176]. Furthermore, the gut microbiota controls the endocrine activities of the intestine; for example, SCFAproducing bacteria, which are reduced in CVD cases [28,151,153,154], promote secretion of incretins with cardioprotective, antiatherogenic, and antihypertensive properties [177][178][179][180], except for PYY [181,182]. Therefore, the gut dysbiosis seen in CVD cases gives rise to an endocrine environment favoring CVD development.…”
Section: Gut-heart Crosstalk and Inflammation In The Development Of Cvdmentioning
confidence: 99%